(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article focuses on the concept of museum identity, activities, tasks, development in Europe in this area is rapidly progressing, museum identity is also developing in Uzbekistan, and conclusions are drawn.